2016
DOI: 10.4143/crt.2015.481
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Significance of Tyrosine Hydroxylase mRNA Transcripts in Peripheral Blood at Diagnosis in Patients with Neuroblastoma

Abstract: PurposeThe purpose of this study is to investigate the clinical significance of tyrosine hydroxylase (TH) expression in peripheral blood (PB) at diagnosis in patients with neuroblastoma.Materials and MethodsTH mRNA expression in PB was measured by reverse transcription quantitative real-time polymerase chain reaction in 210 patients who were newly diagnosed with neuroblastoma from July 2005 to June 2015 and the clinical significance of TH expression in PB at diagnosis was evaluated.ResultsTH expression was pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 25 publications
0
20
0
Order By: Relevance
“…Importantly, to provide sufficient follow-up data, the analy- Many studies have explored potential methods of identifying HR-NBL patients with particularly poor outcomes. These include quantification of tumour-related mRNA in blood or BM samples, 10,26,27 semi-quantitative scoring of mIBG response, 8,9,28 identification of specific tumour genetic aberrations such as ALK mutation or TERT rearrangements [29][30][31] and multiple different gene expression classifiers. [32][33][34] As yet, these techniques have not yet been simultaneously evaluated in sufficiently large homogeneously treated HR-NBL patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Importantly, to provide sufficient follow-up data, the analy- Many studies have explored potential methods of identifying HR-NBL patients with particularly poor outcomes. These include quantification of tumour-related mRNA in blood or BM samples, 10,26,27 semi-quantitative scoring of mIBG response, 8,9,28 identification of specific tumour genetic aberrations such as ALK mutation or TERT rearrangements [29][30][31] and multiple different gene expression classifiers. [32][33][34] As yet, these techniques have not yet been simultaneously evaluated in sufficiently large homogeneously treated HR-NBL patient populations.…”
Section: Discussionmentioning
confidence: 99%
“…Biochemical analysis evidenced a decrease of neuronal biomarkers expression and a significant increase of TH, DBH, NSE and CgA, indexes of neuroendocrine differentiation and considered unfavorable prognostic neuroblastoma biomarkers [ 34 ]. In a recent study, Lee and colleagues [ 35 ] evaluated the clinical significant of TH mRNA transcripts levels in the peripheral blood of patients with neuroblastoma demonstrating that TH expression was associated with high-risk features, advanced stage and worse outcome. Previous studies also reported that positive TH expression was a poor prognostic indicator in metastatic neuroblastoma [ 36 , 37 ], suggesting a role of this marker in stratification.…”
Section: Discussionmentioning
confidence: 99%
“…As with immunocytochemical analyses, RT-PCR-based studies have consistently identified NB-specific mRNA in peripheral blood at diagnosis in patients with metastatic disease and in a fraction of patients with localized and stage 4S disease (table 4). Diagnostic TH mRNA levels and CTC counts are typically higher in patients with more advanced metastatic disease [185,204,206,212] and in patients with high-risk disease [206,212], as observed in other solid malignancies [166]. However, NB-specific mRNA levels and CTC counts do not correlate with MYCN status [182,184,206,207,212].…”
Section: Emerging Tumour-specific Circulating Biomarkers In Neuroblasmentioning
confidence: 99%
“…In addition to serving as a potential diagnostic biomarker, there is a wealth of evidence supporting the prognostic value of NB-specific mRNA, with numerous studies reporting a correlation between mRNA levels and survival outcomes (table 4). High transcript levels of TH and other NB-specific genes at diagnosis have been associated with poor OS and/or EFS in patients with localized and metastatic disease, independent of risk status [187,193,194,197,203,206,208]. Similarly, high CTC counts (≥ 10 cells per 4 ml blood) have recently been shown to correlate with poor OS [212].…”
Section: Emerging Tumour-specific Circulating Biomarkers In Neuroblasmentioning
confidence: 99%
See 1 more Smart Citation